Learning Strategies in Enterprises: empirical findings, implications and perspectives for the immediate future. (27th April 2016) - Brandi, Ulrik; Iannone, Rosa Lisa
Abstract : The article examines learning strategies at the enterprise level, conceptualising them into three main dimensions: learning systems and incentives, connecting to the affective dimension of learning which behavioural learning addresses effectively; skills' development, chiefly addressing the cognitive dimension of learning to which cognitive and action learning principles can be applied; and, work design and the organisation of work, which attend to the structural dimension of learning and socio‐cultural approaches. Through this conceptual understanding, we empirically explored the learning strategies of 194 enterprises, searching for the most pressing needs and commitments to learning. Our results show that enterprises struggle to find the optimal balance between the use of systematic and ad‐hoc arrangements of learning systems and incentives, yet they must emphasise intrinsic needs as a key business strategy, systematise certain aspects of HR, whilst minimising the negative effects of status distinction, hierarchy and bureaucracy. They must also address the pervasive effects of stress and burnouts. Most especially, enterprises must address the gap between the high valuation of soft skills and the low investment in developing them. Methods equipping enterprises with clear calculations for return on investment in soft skills' training are needed. These issues can be effectively addressed by strengthening networks and communities of practice, fostering greater awareness of public funds and public‐sponsored opportunities, investing in public‐private research and backing the greater recognition of on‐the‐job learning.